Injectivity in Congruence Distributive Equational Classes - Day, Richard Alan (My University, 1970)
In this thesis, we study the concept of injectivity in equational classes of (universal) algebras and in particular we are concerned with congruence distributive equational classes that have enough injectives. We show that every reasonable equationally complete congruence distributive equational class has enough injectives and we describe them completely. We then examine what equational subclasses of Lattices, Heyting algebras, and pseudo-complemented lattices have enough injectives.
Keywords: injectivity, equational classes, congruence, distributive, lattices